Effectiveness of Hajj Psychology Training to Improve Emotional Intelligence Prospective Pilgrims - Ahmad Razak; Muhammad Ahkam Alwi; Ahmad Yasser Mansyur; Tarmizi Thalib (Journal of Educational Science and Technology (EST), 2024)
Emotional intelligence is one of the keys to success in Hajj worship. Emotional intelligence is the ability to manage emotions to improve the quality of one's own life and relate to others. Training is needed to give the candidate Hajj Jamaah an understanding of the importance of emotional intelligence. The research is aimed at improving the emotional intelligence of Hajj candidates. One hundred candidates from the city of Makassar who are 20 years of age and older are involved in this study. It consists of over 50 subjects as control and 50 as experimental groups. Emotional intelligence is measured by the Emotional Intelligence Test Scale (EIT). Psychological training focuses on developing self-awareness, self-control, self-motivation, empathy, and social skills. The study uses an experimental approach (pretest post-test control group design), with statistical analysis techniques T-Test Between two independent sample means. The research results indicate that the psychological training of Hajj effectively improves the emotional intelligence of the candidate Hajj Jamaah. Psychological training can help a candidate Jamaah Haji to become a more calm, patient, and empathic Jamaah. This is important because the Hajj Jamaah will face various challenges during Hajj worship, both physical and mental